Penetapan Denda Pada Akad Tabarru - Saipul Azis; Rozalinda (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Tabarru and 'Ariyah have a relationship as a unit where 'Ariyah is a contract that is part of the Tabarru contract, namely a contract intended to do good without any strings attached to compensation. Famous fines are found in commercial matters, this becomes a problem when fines are inserted or even applied to the 'Ariyah contract, which incidentally is a contract that is meant to only hope for the pleasure of Allah. The method used in this study is to use a qualitative method where the operational research is in the form of descriptive which emphasizes understanding the meaning of an object. The data sources used are in the form of literature and articles that have relevance to the research, the data collection technique used is literature study, and data analysis techniques are carried out in the form of reduction, presentation, and conclusion of data. The results of the study show that some scholars allow fines because there are many arguments ordering them to keep the contract (agreement), and in terms of Fath al-Dzari'ah can implement fines on the tabarru contract which is a legitimate thing to do and does not violate the terms of the contract. So that in determining fines on the contract of Tabaru it is permissible with the intention of doing good and not causing harm to the parties involved